The Development and Implementation of a Tool for Encouraging the Practice of Student-Driven Documentation in Engineering Design - Bitetti, Susan. (2017)
Abstract: With the increase of engineering design activities in K-12 classrooms comes a new set of challenges to educators and policy-makers. Previous studies have demonstrated the benefits of incorporating design tasks into formal education curriculum; however, a gap in research still remains surrounding how additional scaffolds can best support students and teachers in these less traditional learning activities. In this thesis, I will discuss the development, design, implementation, and evaluation of one particular tool, a documentation station, made with the intent of supporting engineering design tasks within formal education settings. I set out to create a tool that would not only encourage sketching, which has been long established as a valued skill of the engineering discipline, but would also allow for other multimodal representations. Due to the iterative nature of the design and testing of the documentation station, student tendencies around documentation could be observed in response to the changes in design of the tool itself and the different kinds of engineering design tasks in which the students engaged. Analysis of classroom video footage, student-generated content, and survey data suggest that students and teachers found different affordances and drawbacks to the documentation station and the practice of documentation itself. This research will detail the motivation behind the creation of the documentation station, the design methodology and the resulting tool, and what insights surrounding student documentation practices could be gained through its testing.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Chris Rogers.; Committee: Chris Rogers, Ethan Danahy, and Kristen Wendell.; Keywords: Mechanical engineering, and Design.